The Implementation of Drumband Extracurricular Activities in Character Building of Students at SD Negeri 3 Pagar Alam - Dewi, Ratih Mustika; Hermi, Hermi (The Future of Education Journal, 2025)
This study aims to determine the implementation of the Drumband extracurricular activity in character building at SD Negeri 3 Pagar Alam, as well as to identify the factors that hinder its effectiveness. The background of this study is the lack of good character, particularly in teamwork, which is caused by the absence of mutual help among peers. The method used in this study is descriptive qualitative research with data collection techniques including observation, interviews, and documentation. The population of this study includes all students participating in the Drumband extracurricular activity at SD Negeri 3 Pagar Alam, totaling 133 students. The sample consists of 70 fifth-grade students who participate in the Drumband extracurricular activity. The results show that the Drumband extracurricular activity can contribute to character development in students. The obstacles identified include limited time, a shortage of Drumband instructors, the diverse character traits of students, and limited supporting facilities and infrastructure.